2004
DOI: 10.1002/ijc.20423
|View full text |Cite
|
Sign up to set email alerts
|

Childhood body mass index and later cancer risk: A 50‐year follow‐up of the Boyd Orr study

Abstract: Associations between childhood BMI and adult cancer risk were investigated in a historical cohort study based on the Carnegie ("Boyd Orr") Survey of Diet and Health in PreWar Britain (1937-9). In 14 centres in England and Scotland, children had their height and weight measured. We included 2,347 individuals aged between 2 and 14 years 9 months at the time of measurement, who were traced through the National Health Service Central Register. Relative cancer risk (registration or death) was estimated in relation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 31 publications
1
43
1
Order By: Relevance
“…A meta-analysis of adult BMI revealed a stronger association with colon than rectal cancer [31]. The few studies that have examined early life BMI and later colorectal cancer risk indicated either no association [32][33][34] or a positive relationship [6,10,35,36], as with our study. The largest comparable study, in which height and weight were measured (rather than self-reported) at age 15 years, is a follow-up of participants in a tuberculosis screening program in Norway [37].…”
Section: Colorectal Cancercontrasting
confidence: 56%
“…A meta-analysis of adult BMI revealed a stronger association with colon than rectal cancer [31]. The few studies that have examined early life BMI and later colorectal cancer risk indicated either no association [32][33][34] or a positive relationship [6,10,35,36], as with our study. The largest comparable study, in which height and weight were measured (rather than self-reported) at age 15 years, is a follow-up of participants in a tuberculosis screening program in Norway [37].…”
Section: Colorectal Cancercontrasting
confidence: 56%
“…On the other hand, few studies have addressed the impact of adolescent overweight and obesity on the incidence of CRC cases later in life (6)(7)(8)(9)(10)(11)(12)(13). The data are inconsistent as some of the studies included few incident cases, whereas other studies included self-reported, rather than measured body mass index (BMI).…”
Section: Introductionmentioning
confidence: 99%
“…The short-and long-term health consequences of elevated BMI in childhood and adolescence remain unclear. While some prospective studies suggest that excess weight gain during these developing years is directly associated with adverse future health outcomes, including incidence of type 2 diabetes (T2D) (4,5) , CVD (6,7) and some cancers (8,9) , others disagree (10)(11)(12) . Studies that fail to show a relationship between childhood weight and disease outcome in adulthood have suggested that significant relationships dissipate when adjusted for adult BMI (12) .…”
mentioning
confidence: 99%